From a traditional medicine monomer to a modern neurotherapeutic scaffold: a review of SAR-Driven tetramethylpyrazine derivatives for cerebrovascular and cognitive health - Wang, Xiaodi; Cao, Muhan; Xu, Yi; Yang, Xifei; Hou, Qinghua (Frontiers in Pharmacology, 2025)
Tetramethylpyrazine (TMP), a bioactive alkaloid isolated from the traditional Chinese medicine Ligusticum wallichii (Chuanxiong), has gained significant attention for its therapeutic potential in cerebrovascular diseases and cognitive impairment, mainly due to its antioxidant, anti-inflammatory, and anti-apoptotic properties. However, its clinical application is often limited by suboptimal pharmacokinetic characteristics and modest potency. This review highlights recent advancements in the structure-activity relationship (SAR) optimization of TMP, focusing on its derivatives’ neuroprotective efficacy and vascular benefits. We specifically emphasize the clinical translational potential of several TMP derivatives, such as T-006, TMP-nitrone hybrids (e.g., TN-2), TMP-piperazine derivatives, and TMP-phenolic acid hybrids (e.g., T-VA). These compounds exhibit markedly improved drug-like properties, including enhanced lipid solubility, oral bioavailability, blood-brain barrier (BBB) permeability, and multi-target neuroprotective actions. Additionally, we critically examine the challenges these TMP derivatives face in clinical translation, such as metabolic instability, hepatotoxicity, and formulation challenges, while discussing current strategies to address these issues. The review concludes by emphasizing the significant promise of these next-generation TMP derivatives as therapeutic candidates for cerebrovascular and neurodegenerative disorders, and their need for further preclinical and clinical exploration to fully realize their therapeutic potential.